(3CNHGQ ecIs - (3eMeO Hf YHO GdcQje GdGRQbj, CHh GdhdjO,J (B223 (3g` s ((3fUQ Hf YHO GdefYe Hf CHj GdhbGQ GdJfhNi s)
(3ChdgG (B:s
(3PcQ eG cGfJ GdcYHI Ydjg ahb GdeGA bHd Cf jNdb Gddg GdSehGJ hGdCQV heG LGA ai Pdc s
(3BNQgG (B:s
(3hGdQGMI Ohf GdMOjHjI Ydi jSGQ GdPGgH Edi LOg GdHZHjHI hGdHZjH HGPGNQ BNQ cJGH ecI MQSgG Gddg JYGdi s
(3GdhQbI GdChdi HNW eZGjQ YdjgG ELGRI HQhGjI GdcJGH HGdGScfOQjI SfI (B631 (3HChdgG agQS HNW eZGjQs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3ecJHI GdeOjfI GdefhQI(B((3JGQjN (B2) s
Keywords: (3GdJGQjNs